2017
DOI: 10.1002/2016jc012178
|View full text |Cite
|
Sign up to set email alerts
|

Storm surge along the Pacific coast of North America

Abstract: Storm surge is an important factor that contributes to coastal flooding and erosion. Storm surge magnitude along eastern North Pacific coasts results primarily from low sea level pressure (SLP). Thus, coastal regions where high surge occurs identify the dominant locations where intense storms make landfall, controlled by storm track across the North Pacific. Here storm surge variability along the Pacific coast of North America is characterized by positive nontide residuals at a network of tide gauge stations f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 46 publications
(84 reference statements)
1
27
0
Order By: Relevance
“…This possibly prevented the classical teleconnections that deliver elevated rainfall to California. Bromirski et al () suggest that changes in the Hadley circulation possibly limited storm surge during the 2015–2016 event compared to other El Niño events. These characteristics make the 2015–2016 El Niño event unusual compared with earlier recorded strong canonical El Niño events where storm tracks are shifted south, creating a more westerly wave approach, generally greater wave exposure, and increased rainfall for Southern California.…”
Section: Enso Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This possibly prevented the classical teleconnections that deliver elevated rainfall to California. Bromirski et al () suggest that changes in the Hadley circulation possibly limited storm surge during the 2015–2016 event compared to other El Niño events. These characteristics make the 2015–2016 El Niño event unusual compared with earlier recorded strong canonical El Niño events where storm tracks are shifted south, creating a more westerly wave approach, generally greater wave exposure, and increased rainfall for Southern California.…”
Section: Enso Discussionmentioning
confidence: 99%
“…Barnard et al (2015) found the contrasting coastal behavior observed on opposite sides of the Pacific most closely follows ENSO compared to other climate indices. However, El Niño characteristics can vary considerably (Capotondi et al, 2015) and associated wave energy levels and storm surges differ widely (Bromirski et al, 2005(Bromirski et al, , 2017. Kao and Yu (2009) broadly categorize El Niño events by the location of the major sea surface warming anomaly: Eastern Pacific (canonical; e.g., 1997-1998) and central Pacific (e.g., 2009Pacific (e.g., -2010.…”
Section: Enso Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We calculated the percent change in sea level between 2010 and 2020 to provide the 2015 starting value corresponding to the gas flux data Bromirski, Flick, and Miller (2017). The hourly average environmental data were calculated as the average of only those values associated with the timing of the chamber measurements.…”
mentioning
confidence: 99%
“…We used the averaged values achieved from our selected time periods to estimate the C and N flux for the winter months (November-March) with increasing frequencies of surge determined by proxy as percent increases corresponding to global mean sea level rise scenarios from year 2020 to 2100 of 0.5 ± 0.02 m (NOAA Intermediate-Low) and of 1.5 ± 0.05 m (NOAA Intermediate-High;Sweet et al, 2017). We calculated the percent change in sea level between 2010 and 2020 to provide the 2015 starting value corresponding to the gas flux data Bromirski, Flick, and Miller (2017). reported that Seattle had 66 extreme surge events (lasting at least 6 hr) over 29 winter seasons(December-February 1980-2008.…”
mentioning
confidence: 99%